Adverse childhood experiences affect the health of middle-aged and older people in China: The multiple mediating roles of sleep duration and life satisfaction - Yin, Haojie; Qiu, Xueying; Zhu, Yan; Yang, Qing (Frontiers in Psychiatry, 2023)
Background: Although a significant amount of literature has examined the association between childhood adversity and adverse health outcomes, which may be affected by sleep duration and life satisfaction. However, this relationship has not been researched in the Chinese population. This study aimed to assess the association between childhood adversity and health outcomes, with sleep duration and life satisfaction as mediators. Methods: A total of 14,693 subjects aged 45 and over from the 2018 China Health and Retirement Longitudinal Study (CHARLS) were included. Taking childhood adversity as the independent variable, the health level of middle-aged and older individuals as the dependent variable, and sleep time and satisfaction as the mediating factors, Mplus8.0 software was used to establish a structural equation model to analyse the link between childhood adversity and health level and to explore the mediating effect of target mediators between childhood adversity and health level. Results: In this study, childhood adversity was positively associated with depression symptoms, activities of daily living, and the number of chronic diseases (r=0.116, 0.026 and 0.050, respectively, P<0.001). Associations between adverse childhood experiences and depressive symptoms, activities of daily living, and number of chronic diseases were mediated by sleep duration and life satisfaction, respectively. Conclusion: Adversity experienced in childhood can affect the health status of middle-aged and older people. By ensuring adequate sleep and improving life satisfaction, health outcomes can be improved, and the negative effects of childhood adversity can be reduced.